2015
DOI: 10.1007/s11250-015-0862-z
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Q fever in one-humped camel population in northeast Iran

Abstract: Coxiella burnetii, an obligate intracellular bacterium, is the causative agent of important zoonotic Q fever. It is the etiological agent of coxiellosis or Q fever in animals and human. This seroepidemiological survey was conducted to determine the seroprevalence of coxiellosis in increasingly camel raised population in vast area of Khorasan (North, South, and Razavi) provinces, northeast Iran. Using cluster random sampling strategy, 167 camels in 11 counties were selected as serum samples. Sera were assayed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…Infection in camels is usually subclinical but it can cause late abortion (Janati Pirouz, Mohammadi, Mehrzad, Azizzadeh, & Nazem Shirazi, 2015). Infected camels shed bacteria in urine, faeces, milk, as well as through placenta (Janati Pirouz et al, 2015).…”
Section: Q Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Infection in camels is usually subclinical but it can cause late abortion (Janati Pirouz, Mohammadi, Mehrzad, Azizzadeh, & Nazem Shirazi, 2015). Infected camels shed bacteria in urine, faeces, milk, as well as through placenta (Janati Pirouz et al, 2015).…”
Section: Q Fevermentioning
confidence: 99%
“…Q fever is an endemic disease in Iran, which is mostly reported in human, domestic animals and ticks from almost all the provinces of the country (Mostafavi et al, 2012). However, there is little information about the epidemiology of coxiellosis in camels (Janati Pirouz et al, 2015). (Motamedi, 1987) 1986-1987 Qazvin RBPT, SAT, 2ME, CFT 77/935 (8%) (Zowghi & Ebadi, 1991) 1994 Isfahan (Najaf Abad) RBPT 5/100 (0.05%) (Miranzade, 1994) 1999 Bushehr RBPT, SAT, 2ME, CFT 5/258 (1.93%) (Khadjeh, Zowghi, & Zarif-fard, 1999) 2005 Isfahan (Najaf Abad) RBPT, Wright, 2ME 11/384 (2.84%) (Pourjafar et al 2005) 2007 Hormozgan RBPT 3/103 (2.91%) (Garib, 2011(Garib, ) 2011 Sistan and Baluchestan RBPT, SAT, 2ME 17/500 (3.4%) (Sargaz, 2011) 2008-2011 Yazd RBPT 149/395 (37.83%) (Sazmand, Rasooli, et al, 2012)…”
Section: Q Fevermentioning
confidence: 99%
“…From the study, a C . burnetii seroprevalence of 28.7% was reported among the camels at the individual animal level [ 119 ]. Among dogs, two studies reported on C .…”
Section: Resultsmentioning
confidence: 99%
“…In the current review, only a single study reported on C . burnetii seroprevalence among one-humped camels drawn from North Khorsan, South Khorsan and Razavi Khorsan provinces, in the northeastern part of the country [ 119 ]. The C .…”
Section: Discussionmentioning
confidence: 99%
“…Seven papers detailed high Q fever Coxiella burnetii seropositivity in camels (Schelling et al 2003;Schelling et al 2004;Vanderburg et al 2014;Pirouz et al 2015;Njeru et al 2016;Mohabbati Mobarez et al 2017;Klemmer et al 2018). Seroprevalence levels of up to 73% were present in camels in Chad (Schelling et al 2004).…”
Section: Bacterialmentioning
confidence: 99%